Resting injured limbs delays recovery: a systematic review. - Nash, C; Mickan, S; Mar, D; Glasziou, P (2004)
OBJECTIVES: Rest is commonly used as primary treatment, rather than just palliation, for injured limbs. We searched the literature for evidence of benefit or harm from immobilization or mobilization of acute limb injury in adults. DATA SOURCES: We systematically searched for and retrieved randomized controlled trials (RCTs) of mobilization or rest for treatment of acute limb injuries, in Medline (1966-2002), EMBASE, Web of Science, and the Cochrane library, in all languages. REVIEW METHODS: We examined patient-centered outcomes (pain, swelling, and cost), functional outcomes (range of motion, days lost from work) and complications of treatment. RESULTS: Forty-nine trials of immobilization for soft tissue injuries and fractures of both upper and lower limbs were identified (3366 patients). All studies reported either no difference between rest and early mobilization protocols, or found in favor of early mobilization. Reported benefits of mobilization included earlier return to work; decreased pain, swelling, and stiffness; and a greater preserved range of joint motion. Early mobilization caused no increased complications, deformity or residual symptoms. CONCLUSIONS: We should not assume any benefit for immobilization after acute upper or lower limb injuries in adults. Rest appears to be overused as a treatment. More trials are needed to identify optimal programs for early mobilization.